Memahami Pajak Penghasilan Final, Fokus pada PPH Pasal 4 Ayat 2 - Stefani Stefani; Anggun Rohaya (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
Theoretical The lion's share of a country's budget comes from tax collection. The most source of subsidizing is charges, which are utilized to advance national growth. Income charges make the foremost cash for the government. One of the purposes of last salary charge is to supply administrations related to leasing arrive and/or buildings, such as leasing rooms. As expressed in Pay Assess Article 4 Passage (2), all company onscreen characters utilize bookkeeping to report all exchanges related to charge collection exercises. Article 4 PPh is connected to the Indonesian economy in this article. Sources of salary subject to this assess incorporate giving development administrations, leasing arrive and buildings, and ensuring property rights. This article highlights the ease of tax assessment, installment and charge detailing as an exertion to cut authoritative costs for both citizens and the Directorate General of Charges (DJP). This research could be a subjective technique; Particularly, it could be a writing survey that employments numerous citations from freely accessible sources. The creator offers a subjective strategy by illustrating how PPh section 2 article 4 is connected within the financial segment. This investigate found that by emphasizing responsibility and openness in money related exercises, the execution of this charge has made a difference grow the Indonesian economy.